Strength relations in phonology - Nasukawa, Kuniya, 1967-; Backley, Phillip (Studies in generative grammar ;, 2009)
This collection of papers focuses on the general theme of phonological strength, bringing together current work being undertaken in a variety of leading theoretical frameworks. Its aim is to show how referring directly to strength relations can facilitate explanation in different parts of the phonological grammar. The papers introduce illuminating data from a wide range of languages including English, Dutch, German, Greek, Japanese, Bambara, Yuhup, Nivkh, Sesotho and other Bantu systems, demonstrating how strength differences are central to the analysis of phonological patterning not only in we.